PERAN KEPALA MADRASAH DALAM MENINGKATKAN KINERJA ADMINISTRASI PENDIDIKAN UNTUK PENGEMBANGAN SUMBER DAYA MANUSIA DI SMKS DAYAH DARUL IHSAN ACEH BESAR - Nurussalami Nurussalami (Lembaga Sepercenter, 2025)
The problems that arise in the field include the lack of competence of administrative staff in managing personnel data and planning programmes to improve teacher capacity. In addition, the use of information technology to support educational administration is still limited, so that human resource data management is not yet running efficiently and accountably. Coordination between the administration and the school management team is also not very synergistic, which has an impact on the slow implementation of training, certification, or competency improvement programmes for education personnel in schools. This study aims to examine the role of madrasah principals in improving educational administration performance as a strategic effort in human resource development at SMKS Dayah Darul Ihsan Aceh Besar. The research approach used is a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation.The results show that the madrasah principal plays an important role as a leader, manager, and motivator in directing an efficient, orderly, and organised educational administration system. Various strategies were implemented to improve administrative performance, such as staff training, continuous coaching, the application of information technology, and the establishment of a professional work culture. Factors influencing administrative performance included leadership, administrative staff competence, infrastructure, work climate, and policy support.Good administrative performance has a proven positive impact on human resource development, particularly in terms of improving the competence, productivity, and professionalism of teachers and educational staff. Thus, the role of the madrasah principal is crucial in creating an administrative system that supports the achievement of educational goals and the development of quality human resources.